MEMBEDAH TUJUAN PENDIDIKAN MUHAMMADIYAH - Ali, Mohamad (Profetika, 2016)
The presence of modern religious school âMuhammadiyahâ (1911) be a trigger asthe establishment of modern organizations: Muhammadiyah (1912). Long time before Indonesiaâsindependence, Muhammadiyah has formulated educational goals for schools which arebuilt.Since its establishment until today, the purpose of Muhammadiyah education amendedseveral times. These changes are a creative response of Muhammadiyah on current socialchange, a shift in the orientation of community life, as well as the progress of science andtechnology.from the political constellation of national education, Muhammadiyah was relativelyautonomous when formulating the educational goals.Meanwhile, from the perspectiveof modern educational theory, style of Muhammadiyah educational purposes closer to progressiveeducation theory that emphasizes the experience reconstruction continuously as a vehicleto promote social life.eKeywords: educational; Muhammadiyah education; progressive.Abstrak: Kehadiran sekolah agama modern âMuhammadiyahâ (1911) menjadi trigger berdirinyaorganisasi modern: Muhammadiyah (1912). Jauh sebelum Indonesia merdeka, Muhammadiyahtelah merumuskan tujuan pendidikan bagi sekolah-sekolah yang diselenggarakannya.Sejak awal berdiri hingga saat ini, tujuan pendidikan Muhammadiyah mengalamibeberapa kali perubahan. Perubahan-perubahan itu merupakan respons kreatif Muhammadiyahatas arus perubahan sosial, pergeseran orientasi kehidupan masyarakat, maupun kemajuanilmu dan teknologi. Dilihat dari konstelasi politik pendidikan nasional, Muhammadiyahternyata relatif mandiri ketika merumuskan tujuan pendidikannya. Sedangkan dari perspektifteori pendididkan modern, corak tujuan pendidikan Muhammadiyah lebih mendekati teoripendidikan progresif yang menekankan pada rekonstruksi pengalaman secara terus-menerussebagai wahana memajukan kehidupan sosial.Kata Kunci: tujuan pendidikan; pendidikan Muhammadiyah; progresif.